2020
DOI: 10.1177/1836939120936002
|View full text |Cite
|
Sign up to set email alerts
|

Writing letters to characters in bullying-themed stories: An approach to educating about bullying in early childhood

Abstract: In spite of increasing international concern and the long-term effects of bullying on children’s development, bullying in early childhood has been overlooked and underestimated, with both children and adults having difficulties in recognizing and understanding it. This study explores how young children respond to bully-themed stories, what and how they expressed in writing letters to characters from the stories, and how their attitudes towards and understanding of bullying have changed through a series of read… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 21 publications
2
7
0
1
Order By: Relevance
“…Researchers were also interested in responses before and after the storybook read-aloud when participants acted as the bystander in a common bullying scenario. When results were analyzed by age, results indicated that 5-year-olds were more likely to engage in direct action after reading the storybook read-aloud than before reading, which is consistent with previous work with 5-year-olds and bullying-related books (Wee et al, 2022a;Wee & Lee, 2020). These findings are notable as the book utilized in the class reading discussed both direct and indirect behaviors and presented them both as options for dealing with a bully.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Researchers were also interested in responses before and after the storybook read-aloud when participants acted as the bystander in a common bullying scenario. When results were analyzed by age, results indicated that 5-year-olds were more likely to engage in direct action after reading the storybook read-aloud than before reading, which is consistent with previous work with 5-year-olds and bullying-related books (Wee et al, 2022a;Wee & Lee, 2020). These findings are notable as the book utilized in the class reading discussed both direct and indirect behaviors and presented them both as options for dealing with a bully.…”
Section: Discussionsupporting
confidence: 89%
“…Finally, researchers were interested in preschoolers' changing conceptualizations of a bully after being exposed to a storybook read-aloud addressing bullying behavior. Results indicated that participants were more likely to correctly identify what a bully was after engaging in the read-aloud, consistent with Wee and Lee's (2020) study. This indicates a rudimentary understanding of bullying behavior at a young age, consistent with other findings (Camodeca et al, 2015;Monks et al, 2005;Vaillancourt et al, 2008).…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Metode yang digunakan adalah: bercerita, tanya jawab, diskusi dan praktik langsung. Dalam penanaman karakter anak, diskusi mengenai suatu nilai meningkatkan pemahaman anak mengenai suatu karakter, membangun empati, melatih anak menunjukkan beragam cara pemecahan masalah dan membuat perencanaan efektif dalam mengimplementasi suatu nilai dalam keseharian mereka (Wee & Lee, 2020). Saat berada di rumah, orang tua dapat menceritakan kembali kisah tokoh inspiratif, melakukan tanya jawab, diskusi bersama nilai karakter kebangsaan, gerak dan lagu bersama serta melakukan aktivitas penguatan karakter kebangsaan bersama anak.…”
Section: Prosedur Penggunaan Paket Pembelajaranunclassified